Estado de la conservacion ex situ de los recursos geneticos de quinua - Food and Agriculture Organization of the United Nations; Rojas, W.; Pinto, M.; Centre de coopération internationale en recherche agronomique pour le développement; Bioversity International; Alanoca, C.; Gómez Pando Pedro Leon-Lobos, L.G.; Alercia, A.; Diulgheroff, S.; Padulosi, S.; Bazile, Didier (Food and Agriculture Organization of the United Nations, 2014)
The chapter provides an overview of the status of ex situ conservation of quinoa genetic resources around the world. it does also introduces its agro-morphological variation through descriptor lists, evaluation and documentation activities. The analysis is complemented by a lessons learnt sharing through a number of international projects focusing on the sustainable conservation and use in Latin America.